2005
DOI: 10.1093/poq/nfi054
|View full text |Cite
|
Sign up to set email alerts
|

Ballot Design and Unrecorded Votes on Paper-Based Ballots

Abstract: The 2000 presidential election focused attention on the problem of unrecorded votes, in which a person casts a ballot but fails to record a valid vote for a particular contest. Although much recent research has evaluated voting technologies and their effects on unrecorded votes, there has been little research on the effects of ballot design. We argue that the same theories used to design and evaluate self-administered surveys can be used to analyze ballot features. We collect and code paper-based ballots used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
87
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 28 publications
2
87
0
3
Order By: Relevance
“…A relatively higher rate of overvotes resulting in spoiled ballots was found in precincts with more black residents (Neely and Cook 2008). This follows work that has examined the residual vote (Bullock and Hood 2002;Darcy and Schneider 1989;Kimball et al 2004;Kimball and Kropf 2005) and overvotes, in particular (Sinclair and Alvarez 2004). 5 Higher counts of overvotes were also found, at times, among San Francisco communities with more Latino residents (Neely and Cook 2008), something shown in a similar analysis of voters in Los Angeles (Sinclair and Alvarez 2004), and in areas with more foreignborn residents.…”
Section: Literature and Hypothesesmentioning
confidence: 71%
See 2 more Smart Citations
“…A relatively higher rate of overvotes resulting in spoiled ballots was found in precincts with more black residents (Neely and Cook 2008). This follows work that has examined the residual vote (Bullock and Hood 2002;Darcy and Schneider 1989;Kimball et al 2004;Kimball and Kropf 2005) and overvotes, in particular (Sinclair and Alvarez 2004). 5 Higher counts of overvotes were also found, at times, among San Francisco communities with more Latino residents (Neely and Cook 2008), something shown in a similar analysis of voters in Los Angeles (Sinclair and Alvarez 2004), and in areas with more foreignborn residents.…”
Section: Literature and Hypothesesmentioning
confidence: 71%
“…However, because those differences were rare in the earlier IRV analysis (Neely and Cook 2008) we expect there to be no significant difference in overvotes between areas with more male or female residents. Other factors have been shown to matter in the rate at which voters cast uncounted ballots: elderly voters (Darcy and Schneider 1989;Kimball and Kropf 2005;Stiefbold 1965), less educated voters (Walker 1966;Bullock and Hood 2002), and poorer voters (Darcy and Schneider 1989;Kimball, Owens, and Keeney 2004;Knack and Kropf 2003) have been identified as more likely to cast a ballot that is not counted. However, the prior IRV study found few of these relationships.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…A relatively higher rate of overvotes resulting in spoiled ballots was found in precincts with more black residents (Neely and Cook 2008). This follows work that has examined the residual vote (Bullock and Hood 2002;Darcy and Schneider 1989;Kimball et al 2004;Kimball and Kropf 2005) and overvotes, in particular (Sinclair and 5 Alvarez 2004). 5 Higher counts of overvotes were also found, at times, among San Francisco communities with more Latino residents (Neely and Cook 2008), something shown in a similar analysis of voters in Los Angeles (Sinclair and Alvarez 2004), and in areas with more foreignborn residents.…”
Section: Literature and Hypothesesmentioning
confidence: 96%
“…In his critique of the new polling methods Sullivan (2009) found that Internet respondents who are surveyed multiple times per week on different topics develop survey fatigue as they pursue prizes like tote bags, gift certificates, T-shirts and even cash. Though studies on ballot design (eg, Kimball & Kropf 2005;denver, Johns & Carman 2009) have attempted, using survey theories, to investigate the features of ballot designs and their impact on voting errors the issue still rests on the reliability of the method and measures. Exceptions are when there are similarities between the designs of ballot papers and of surveys.…”
Section: Reliability Of Survey Resultsmentioning
confidence: 99%